Structured autocorrelation matrix estimation for coprime arrays - Chachlakis, Dimitris G.; Markopoulos, Panos P. (Signal processing, 2021)
•Structure properties of the nominal coarray’s autocorrelation matrix are studied.•A novel structured coarray autocorrelation matrix estimate is proposed.•Structured coarray autocorrelation matrix estimation enables superior DoA estimation. A coprime array receiver processes a collection of received-signal snapshots to estimate the autocorrelation matrix of a larger (virtual) uniform linear array, known as coarray. By the received-signal model, this matrix has to be (i) Positive Definite, (ii) Hermitian, (iii) Toeplitz, and (iv) its noise-subspace eigenvalues have to be equal. Existing coarray autocorrelation matrix estimates satisfy a subset of the above conditions. In this work, we propose an optimization framework which offers a novel estimate satisfying all four conditions:  we propose to iteratively solve a sequence of distinct structure-optimization problems and show that, upon convergence, we provably obtain a single estimate satisfying (i)-(iv). Numerical studies illustrate that the proposed estimate outperforms standard counterparts, both in autocorrelation matrix estimation error and Direction-of-Arrival estimation.